The relevance of the concept of semantic field in linguistics - Sobirova Feruza Islomjon qizi (Euro Asian Journal Publishing, 2024)
This article provides more details about the relevance of the concept of a semantic field. The article outlines the true nature of the semantic field theory of linguistics and examines a number of opinions on the theory of semantic field in world and world and Uzbek linguistics .
Keywords: concept; semantics; field; time